The Treatment of the Cubital Tunnel Syndrome Using the Anterior Transposition Surgical Technique - Catalin Gheorghe BEJINARIU; Laura Mihaela BOGHIAN; Siramona POPESCU; Silviu Adrian MARINESCU (Modern Medicine)
Introduction: The paper aims to present the advantages and disadvantages related to using the anterior transposition technique for the treatment of the cubital tunnel syndrome. Materials and Methods: The study presents the surgical treatment of a 58 years old woman. The therapeutic protocol included the decompression of the ulnar nerve at the level of the elbow, followed by the anterior transposition, the new position being maintained by anchoring in a fascial sling. Results: The electromyographic evaluation performed 12 months after the surgical intervention indicated that the parameters of motor nerve conduction were within normal limits on all segments, normal sensory velocities from the V ﬁnger, orthodromic and from the dorsal branch, sign of a very good postoperative recovery. Conclusions: Anterior transposition of the ulnar nerve may be a ﬁrm solution for the treatment of the compressive ulnar neuropathies located at the level of the elbow.